2021
DOI: 10.3389/fpsyt.2021.707342
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Outcomes and Associated Factors Among the International Students Living in China During the COVID-19 Pandemic

Abstract: Background: The emergence of coronavirus disease 2019 (COVID-19) has created a severe mental health problem for international students living in China. Despite the little information on the psychological impact on international students, we aimed to assess the psychological outcomes and associated factors among international students currently living in China during the COVID-19 pandemic.Methods: An online cross-sectional survey was conducted from May 28, 2020 to June 12, 2020 on 402 full-time international st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 64 publications
4
35
0
Order By: Relevance
“…Multi-factor analysis in our study found that the risk of depression and anxiety was significantly increased among males, which was consistent with the findings from previous studies ( 28 , 44 , 45 ) Online learning at home requires greater self-discipline to complete online courses, particularly in the earlier period when students are adapting to the new system ( 34 ). Self-regulation and self-management ability are very important in the process of online learning ( 46 ).…”
Section: Discussionsupporting
confidence: 92%
“…Multi-factor analysis in our study found that the risk of depression and anxiety was significantly increased among males, which was consistent with the findings from previous studies ( 28 , 44 , 45 ) Online learning at home requires greater self-discipline to complete online courses, particularly in the earlier period when students are adapting to the new system ( 34 ). Self-regulation and self-management ability are very important in the process of online learning ( 46 ).…”
Section: Discussionsupporting
confidence: 92%
“…We searched PubMed on 12 November 2021 using keywords including “international students” and “COVID-19,” and found 15 articles exploring the stress and mental health of international students studying in China ( 16 20 ), South Korea ( 21 ), U.K. ( 15 , 22 ), U.S. ( 15 , 23 ), Australia ( 24 , 25 ), Russia ( 26 ), Turkey ( 27 ), and Poland ( 28 , 29 ). Six studies were on Chinese or Asian international students ( 15 , 21 23 , 25 , 29 ) and nine studies focused on students of other ethnicities ( 16 20 , 24 , 26 28 , 30 ). We found no qualitative articles that systematically investigated COVID-19-related stressors, coping and positive and negative impacts in international students during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…We searched PubMed on 12 November 2021 using keywords including "international students" and "COVID-19, " and found 15 articles exploring the stress and mental health of international students studying in China (16)(17)(18)(19)(20), South Korea (21), U.K. (15,22), U.S. (15,23), Australia (24,25), Russia (26), Turkey (27), and Poland (28,29). Six studies were on Chinese or Asian international students (15, 21-23, 25, 29) and nine studies focused on students of other ethnicities (16-20, 24, 26-28, 30).…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, control and prevention measures such as lockdown, reduction of social contact and changes of teaching mode interrupted the students' daily life, hampered their studies and negatively impacted their psychological health (2). Moreover, previous studies revealed that the international students were more prone to psychological problems because, compared with their domestic peers, they lacked resources to counteract stress and had to cope with more challenges unique to them, such as the language barrier and culture shock (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies were done in western countries, and the research in Asia has been limited, especially during the COVID-19 pandemic. According to the results of a recent survey to the international students, 73.4, 76.6, and 58.5% of the participants had depression, anxiety and stress symptoms, respectively, during the pandemic, and male students presented more symptoms of depression and anxiety than females due to their more risk-taking behaviors (2). As international medical students will be incorporated into the future work force safeguarding the health of mankind, their wellbeing especially their mental health during the pandemic should arouse our attention.…”
Section: Introductionmentioning
confidence: 99%